The Impact of Velocity of Movement on Performance Factors in Resistance Exercise - Hatfield, Disa L.; Kraemer, William J.; Spiering, Barry A.; Häkkinen, Keijo; Volek, Jeff S.; Shimano, Tomoko; Spreuwenberg, Luuk P.B.; Silvestre, Ricardo; Vingren, Jakob L.; Fragala, Maren S.; Gómez, Ana L.; Fleck, Steven J.; et al. (Journal of strength and conditioning research, 2006)
The purpose of this study was to determine the impact of a very slow (VS) velocity and a self-selected volitional (VOL) velocity at varying intensities on repetition number, peak force, peak power, and total volume in the squat and shoulder press exercises. On separate testing days, 9 resistance trained men (age: 23.9 +/- 2.5 years; height: 174.8 +/- 6.5 cm; body mass: 80.1 +/- 12.4 kg) performed a squat (SQ) and shoulder press (SP) exercise at 60 or 80% of 1 repetition maximum (1RM) at either VOL or VS (10-second eccentric and 10-second concentric actions) velocity for as many repetitions as possible. Force, power, and volume (repetitions x kg) were also determined. Subjects performed significantly fewer repetitions (p < or = 0.05) in the VS exercises (60% VS SQ 5 +/- 1 vs. VOL SQ 24 +/- 2; 80% VS SQ 2 +/- 0 vs. VOL SQ 12 +/- 1; 60% VS SP 4 +/- 1 vs. VOL SP 14 +/- 2; 80% VS SP 1 +/- 0 vs. VOL SP 6 +/- 1). Peak force and power were significantly higher at the VOL speed (peak force [in newtons]: 60% VS SQ 564.4 +/- 77.3 vs. VOL SQ 1229.0 +/- 134.9 N; 80% VS SQ 457.3 +/- 27.9 vs. VOL SQ 1059.3 +/- 104.7 N; 60% VS SP 321.6 +/- 37.8 vs. VOL SP 940.7 +/- 144.8 N; 80% VS SP 296.5 +/- 24.7 vs. VOL SP 702.5 +/- 57.7 N; and peak power [in watts]: 60% VS SQ 271.2 +/- 40.1 vs. VOL SQ 783.2 +/- 129.1 W; 80% VS SQ 229.3 +/- 49.5 vs. VOL SQ 520.2 +/- 85.8 W; 60% VS SP 91.3 +/- 21.9 vs. VOL SP 706.6 +/- 151.4 W; 80% VS SP 78.1 +/- 19.8 vs. VOL SP 277.6 +/- 46.4 W). VOL speed elicited higher total volume than the VS velocity. The results of this study indicate that a VS velocity may not elicit appropriate levels of force, power, or volume to optimize strength and athletic performance.The purpose of this study was to determine the impact of a very slow (VS) velocity and a self-selected volitional (VOL) velocity at varying intensities on repetition number, peak force, peak power, and total volume in the squat and shoulder press exercises. On separate testing days, 9 resistance trained men (age: 23.9 +/- 2.5 years; height: 174.8 +/- 6.5 cm; body mass: 80.1 +/- 12.4 kg) performed a squat (SQ) and shoulder press (SP) exercise at 60 or 80% of 1 repetition maximum (1RM) at either VOL or VS (10-second eccentric and 10-second concentric actions) velocity for as many repetitions as possible. Force, power, and volume (repetitions x kg) were also determined. Subjects performed significantly fewer repetitions (p < or = 0.05) in the VS exercises (60% VS SQ 5 +/- 1 vs. VOL SQ 24 +/- 2; 80% VS SQ 2 +/- 0 vs. VOL SQ 12 +/- 1; 60% VS SP 4 +/- 1 vs. VOL SP 14 +/- 2; 80% VS SP 1 +/- 0 vs. VOL SP 6 +/- 1). Peak force and power were significantly higher at the VOL speed (peak force [in newtons]: 60% VS SQ 564.4 +/- 77.3 vs. VOL SQ 1229.0 +/- 134.9 N; 80% VS SQ 457.3 +/- 27.9 vs. VOL SQ 1059.3 +/- 104.7 N; 60% VS SP 321.6 +/- 37.8 vs. VOL SP 940.7 +/- 144.8 N; 80% VS SP 296.5 +/- 24.7 vs. VOL SP 702.5 +/- 57.7 N; and peak power [in watts]: 60% VS SQ 271.2 +/- 40.1 vs. VOL SQ 783.2 +/- 129.1 W; 80% VS SQ 229.3 +/- 49.5 vs. VOL SQ 520.2 +/- 85.8 W; 60% VS SP 91.3 +/- 21.9 vs. VOL SP 706.6 +/- 151.4 W; 80% VS SP 78.1 +/- 19.8 vs. VOL SP 277.6 +/- 46.4 W). VOL speed elicited higher total volume than the VS velocity. The results of this study indicate that a VS velocity may not elicit appropriate levels of force, power, or volume to optimize strength and athletic performance.